2016
DOI: 10.1155/2016/5637072
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-Assisted Percutaneous Cholangiography in Biliary Atresia Diagnosis: Comparison with Open Technique

Abstract: Introduction. Biliary atresia is a surgical cause of prolonged jaundice, which needs to be diagnosed with cholangiography that has traditionally been performed via laparotomy. Laparoscopic assistance has lately been introduced to avoid unnecessary laparotomy. We aim to evaluate the benefits of the laparoscopy-assisted cholangiography and compare it to the traditional procedure via laparotomy. Patients and Method. The medical records of the cases who had undergone cholangiography for prolonged jaundice between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…They further conclude that MMP-7 may be helpful in the diagnosis of BA, but it is far from a new diagnostic "gold standard" (27). Surgical consultation may be delayed given the hesitancy from pediatric teams due to perceived morbidity of surgical intervention (28). At our institution, pediatric surgery is consulted for consideration of laparoscopic cholangiogram and laparoscopic liver biopsy after medical workup for hyperbilirubinemia has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…They further conclude that MMP-7 may be helpful in the diagnosis of BA, but it is far from a new diagnostic "gold standard" (27). Surgical consultation may be delayed given the hesitancy from pediatric teams due to perceived morbidity of surgical intervention (28). At our institution, pediatric surgery is consulted for consideration of laparoscopic cholangiogram and laparoscopic liver biopsy after medical workup for hyperbilirubinemia has been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Inadvertently submitting an infant with Alagille syndrome to a Portoenterostomy based on a false-positive diagnosis of BA can lead to grievous prognostic consequences [ 52 , 53 ]. Technical optimization of cholangiography by radiologists and pediatric surgeons, be it intraoperative or laparoscopic, can increase the method’s accuracy, and avoid an unnecessary portoenterostomy [ 29 , 54 , 55 , 56 ].…”
Section: The First Challenge: Pitfalls In the Diagnosis Of Biliary At...mentioning
confidence: 99%
“…A multicenter study concluded that duct/ductal bile plugs and portal stromal edema were the strongest independent histologic predictors of obstruction[ 17 ]. The sensitivity and specificity of histological findings are over 90%, although histopathological findings similar to those seen in BA may also be observed with other neonatal cholestasis diseases [such as alpha 1 antitrypsin deficiency, progressive familial intrahepatic cholestasis (PFIC), cystic fibrosis], though not necessarily in the early period[ 49 , 50 ]. The absence of an extrahepatic biliary tree in intraoperative cholangiography is, therefore, the leading indicator of BA[ 2 ].…”
Section: Biliary Atresiamentioning
confidence: 99%